Naturally selected : the evolutionary science of leadership - Van Vugt, Mark, 1967-; Ahuja, Anjana (New York : HarperBusiness, 2011)
A psychologist and a scientist examine the history of leadership since the dawn of man, discussing how and why it has evolved over thousands of years and arguing that what people look for in leadership harkens back to humanity's most primordial instincts.
Includes bibliographical references : p. [226]-246 and index.
Keywords: Leadership -- Psychological aspects; Evolutionary psychology